Child Victimization and Polyvictimization Among Young Adults in Northern Chile - Pinto-Cortez, Cristián; Gutiérrez-Echegoyen, Pablo; Henríquez, Diego (Journal of interpersonal violence, 2021)
This study examined the prevalence of victimization and polyvictimization and gender differences in young adults from Arica in northern Chile. In all, 718 college students participated (46.9% men, 53.1% women), aged between 17 and 28 years old (M = 21.6; SD = 4.11). The Spanish version of Juvenile Victimization Questionnaire ( JVQ) was used to access five categories of child victimization (conventional crime, child maltreatment, peer and siblings victimization, sexual victimization, and indirect victimization). In total, 98.7% of young adults reported at least one type of victimization throughout their life. In general, males are more exposed to victimization for conventional crimes and indirect victimization and women to sexual victimization and bullying. A total of 89.1% of the sample was considered polyvictims (i.e., experienced five or more forms of victimization). This research provides information about the epidemiology of victimization and polyvictimization in young adults in the international context, and is the first study from this point of view in a South American country. The results show that young adults in northern Chile experience a high level of victimization, even mostly higher than others studies realized in the international context. Gender is a variable that has a significant influence and must be taken into account in the analyses of this complex subject of study.